Localization of the lipopolysaccharide recognition complex in the human healthy and inflamed premature and adult gut - Wolfs, Tim; Derikx, Joep P.M.; Hodin, Caroline M.I.M.; Vanderlocht, Joris; Driessen, Ann; Bruïne, Adriaan P. de; Bevins, Charles L.; Lasitschka, Felix; Gassler, Nikolaus; Gemert, Wim G. vaon; Buurman, Wim A. (Inflammatory bowel diseases, 2010)
Microbiota in the intestinal lumen provide an abundant source of potentially detrimental antigens, including lipopolysaccharide (LPS), a potent immunostimulatory product of Gram-negative bacteria recognized by the host via TLR-4 and MD-2. An aberrant immune response to LPS or other bacterial antigens has been linked to inflammatory bowel disease (IBD) and necrotizing enterocolitis (NEC).We investigated which cells express MD-2 in the normal and inflamed ileum from neonates and adults by immunohistochemistry. Moreover, MD-2 and TLR4 mRNA expression in normal adult ileum was studied by reverse-transcription polymerase chain reaction (RT-PCR) on cells isolated by laser capture microdissection.Premature infants did not show MD-2 expression either in epithelial cells or in the lamina propria. Similarly, MD-2 was absent in epithelial cells and lamina propria inflammatory cells in preterm infants with NEC. MD-2 protein in the healthy term neonatal and adult ileum was predominantly expressed by Paneth cells and some resident inflammatory cells in the lamina propria. MD-2 and TLR-4 mRNA expression was restricted to crypt cells. Also in IBD, Paneth cells were still the sole MD-2-expressing epithelial cells, whereas inflammatory cells (mainly plasma cells) were responsible for the vast majority of the MD-2 expression.The absence of MD-2 in the immature neonatal gut suggests impaired LPS sensing, which could predispose neonates to NEC upon microbial colonization of the immature intestine. The apparent expression of MD-2 by Paneth cells supports the critical concept that these cells respond to luminal bacterial products in order to maintain homeostasis with the intestinal microbiota in vivo. (Inflamm Bowel Dis 2010;)
Gesehen am 22.04.2024